Towards decentralized and parameterized supervisor synthesis - Lin, Liyong (2015)
This thesis studies the decentralized and parameterized supervisor synthesis problems in the Ramadge-Wonham paradigm. We obtain a characterization of the solvability of the decentralized realization problem, by reducing it to the problem of solving a set of language equations. The close relationship among the problems of language decomposition, supervisor decomposition and decentralized realization is then studied. Complexity-theoretic lower bound proofs are provided by reductions from the language decomposition problem. We then develop complexity reduction techniques for language decomposability verification. A sufficient condition for the undecidability of the distributed supervisor synthesis problem is derived based on the structure of the distributed control architecture. We also present a sufficient condition for the undecidability of a language based parameterized supervisor synthesis problem. The expressive power of the symbolic reachability relations of a class of parameterized systems is investigated and a sound state based parameterized supervisor synthesis procedure is develped in the frameowrk of regular model checking.